Structural and semantic features of abbreviations in the tourism terminology (based on the English language) - Skhalyakho, E. N.; Sasina, S. A.; Bricheva, M. M. (Vestnik Samarskogo universiteta. Istorii͡a︡, pedagogika, filologii͡a, 2025)
The article is devoted to the study of structural and semantic characteristics of abbreviations in the field of tourism. The development of scientific and professional fields and the emergence of new special vocabulary make it relevant to study terms and other units of the language for specific purposes. The tourism sector, as a branch of the economy, is developing dynamically, offering an increasing number of services to its consumers. With the emergence of new types of tourism, new lexical units arise within this subject area. Due to the continuous growth of the tourism terminology, the new vocabulary requires detailed linguistic analysis and systematization, which determines the relevance of the study. Abbreviation is one of the productive ways of word formation in the field of tourism. The purpose of this study is to analyze the structural and semantic features of English abbreviations taken from specialized dictionaries. In the study, the authors used the descriptive method, the method of systematization, the methods of semantic and structural analysis, as well as the method of quantitative counting. The material was classified according to semantic features, identifying a number of lexical and thematic groups that reflect conceptual and categorical features of the tourism sector. The formal characteristics of abbreviations in the tourism subject area are described. Initial abbreviations, clipped words and other types of shortened words are analyzed. Particular attention is paid to a detailed analysis of the structure of abbreviations. The most productive syntactic models for abbreviation making are described. Due to a great number of the names of organizations, which consist of many components, multicomponent abbreviations prevail.